Antibacterial activity test of yen thuo leaf (leeaindica merr) ethanol extract on staphylococcus epdermidis bacteria and its cream production - Muhartri Sanjaya; Nur Cinta Suci Fairu (Institute of Computer Science (IOCS), 2022)
Infection is the process of entry of parasites and contact with the host. Infection occurs when the parasite is able to penetrate or through the host's defenses and live in it. This research was conducted using a parametric experimental method. The parameters used refer to the Indonesian Materia Medika. Antibacterial activity test was carried out by the agar diffusion method using a paper scraper. The parameter measured is the size of the inhibition zone around the paper tray. The results of measuring the pH of the ethanol extract cream preparation of yen thu leaves with observations for 5 weeks showed that the pH of the ethanol extract cream preparations of yen thou leaves did not decrease. The pH of the preparation was determined using a pH meter. The test results on the pH of the cream preparations obtained show that the cream preparations produced are in accordance with the pH of the skin and can be used safely and do not cause irritation to the skin because according to Balsam and Sagarin (1972), the pH of cream preparations suitable for skin pH is between 5 to 8